Stroke-related sarcopenia: a scoping review of influencing factors and clinical outcomes - Yang, Hongyan; Yang, Ting; Wei, Hui (Frontiers in Aging, 2025)
BackgroundStroke-related sarcopenia has attracted increasing attention, and the prevalence is increasing. However, the influencing factors and clinical outcomes are still not well reported in the literature, and existing studies are heterogeneous in terms of study design, outcomes, and means of outcome assessment. We conducted this scoping review to map and summarize the evidence in the rapidly growing field of stroke-related sarcopenia, and guide future research directions.PurposeTo synthesize the influencing factors and clinical outcomes of stroke-related sarcopenia.MethodsThe scoping review process followed the methodological framework of Arksey and O’Malley and was reported using the PRISMA-ScR guideline. Six English databases (PubMed, Embase, CINAHL, Scopus, Web of Science, and the Cochrane Library) were searched from the inception to 13 August 2024, and updated on 5 October 2025. We included studies involving influencing factors and clinical outcomes (concept) of stroke-related sarcopenia (population) in any setting (context).ResultsTwenty-six studies were identified, including six cross-sectional and twenty cohort studies. Forty influencing factors were extracted and integrated into five categories, including demographic, disease, stroke-related, behavioral, and biomarker factors. Stroke-related sarcopenia can cause impaired motor, swallowing, neurological, and psychological function and lead to increased recurrence, readmission, and mortality.ConclusionOur scoping review shows that stroke-related sarcopenia depends on multiple factors and has widespread effects. Understanding these influencing factors and clinical outcomes can help health professionals to intervene and manage stroke-related sarcopenia. However, heterogeneity in the details of the included studies made it difficult to undertake quantitative summaries across studies, more high-quality, multicenter studies should be conducted in the future to provide consistent evidence to guide clinical practice.